Procedure for the quantification of the degradation index of Photovoltaic Generators - Proenza Y. Roger; Camejo C. José Emilio; Ramos H. Rubén (Newinera Publisher, 2021)
A procedure is presented for the quantification of the degradation index of Photovoltaic Generators, based on the quantification of the operational losses inherent in the system, which allows maintaining the nominal operating conditions and by the warranty terms of the photovoltaic generator. A photovoltaic generator connected to the network with a nominal power of 7.5 kWp, installed in the Solar Energy Research Center of Santiago de Cuba, is used to evaluate and validate the procedure. The starting point is the mathematical model of the photovoltaic generator, then the operational losses of the photovoltaic generator are quantified and the mathematical model is adjusted to real conditions, through a polynomial adjustment. The results obtained show that the photovoltaic generator presents deviations in terms of the nominal power generation, because the operational losses are 7% with respect to the values ​​given by the manufacturer.